A java-based enterprise system architecture for implementing a continuously supported and entirely web-based exercise solution. - Zhihui Wang
Since machine-based exercise still uses local facilities, it is affected by time and place. We designed a web-based system architecture based on the Java 2 Enterprise Edition that can accomplish continuously supported machine-based exercise. In this system, exercise programs and machines are loosely coupled and dynamically integrated on the site of exercise via the Internet. We then extended the conventional health promotion model, which contains three types of players (users, exercise trainers, and manufacturers), by adding a new player: exercise program creators. Moreover, we developed a self-describing strategy to accommodate a variety of exercise programs and provide ease of use to users on the web. We illustrate our novel design with examples taken from our feasibility study on a web-based cycle ergometer exercise system. A biosignal-based workload control approach was introduced to ensure that users performed appropriate exercise alone
Keywords: Internet; Java-based enterprise system architecture; Web-based cycle ergometer exercise system; Web-based system architecture; Biosignal-based workload control approach; Conventional health promotion model; Exercise program creators; Functionally distributed design; Machine-based exercise; Self-describing strategy